Investigating The Role Of Communication To Build A Religious Identity Of Islam By Hizbuth Tahrir Indonesia (Hti) In Indonesia - Sovia Sitta Sari, Sovia Sitta Sari (2015)
After the downfall of President Soeharto and New Order regime in 1998, an Islamist groups or known as new religious movement –Hizbuth Tahrir Indonesia (HTI) – sprung up, calling for Islamization of society. Although, approximately 88 per cent of indonesia’s 255 million people are Muslims, according to Islamist new movement’s perception , this country has been ruled under secular values. Moreover, mostly Indonesian muslims practicing Islam have been influenced to secular values also tradition. Muslims’ way of life should be restored to the authenthic Islam which return to the the first age of Islam represented by Prophet Muhammad and The Companion (Khulafaur Rasyidin). In attempting to build an original identity of Islam for Indonesian Muslims, HTI employeed both media and oral communication. This study aimed to describe the process of building Islam identity and the use of communication has been done by the Hizbuth Tahrir Indonesia. To examine the research, the theoretical framework of identity and religious communication was applied. Methodologically, a single case was used in this research to describe the implementation of religious communication and the building identity process. Data will be collected through indepth interviews, and focus group discussions. Multiple sources of data are used to construct triangulation strategies to ascertain the validity of the data.